Human Resource Management Strategies in the Digital Age: Building an Adaptive and Innovative Organization - Bayu Retno; Yeni Yeni; Dian Arlupi Utami; Dhiazumar Falih Gani Ramadhan (Oikonomia : Journal of Management Economics and Accounting, 2025)
Digital transformation has brought significant changes to organizational dynamics and human resource management patterns. The digital era is characterized by developments in information technology, automation, big data, and artificial intelligence, which directly require organizations to change their approach to managing their workforce. This study aims to analyze relevant HR management strategies in the digital era with a focus on building adaptive and innovative organizations. The study method was conducted through an analysis of the latest literature related to digitalization trends, modern HR management models, and best practices in employee competency development. The results of the study show that key strategies include digital talent management, technology-based skills development, digital recruitment systems, data-based performance management, and a collaborative work culture supported by digital platforms. In addition, strengthening soft skills such as creativity, critical thinking, and agility are determining factors for organizational success in facing business environment uncertainty. This research confirms that organizations that are able to integrate HR management strategies with digital technology will be more adept at adapting to change and encouraging continuous innovation. Thus, HR management in the digital age not only functions as a workforce manager, but also as a strategic catalyst in creating long-term competitive advantage